APPLYING COGNITIVE LEARNING STRATEGY IN DEVELOPING THE STUDENTS’ SPEAKING ABILITY - Luqman Luqman (ELTIES : English Language Teaching for EFL Learners, 2020)
This research aimed to examine the types of cognitive learning strategy that the students employed in developing their ability to speak English. This research applied quantitative descriptive and experimental research method. Data were analyzed by descriptive presentation and statistical analysis of t test. This research was carried out at the second year of SMA 2 Sinjai. They are all selected by using random sampling by number of students as sample of 30 students. The researcher conducted questionnaire to capture data about type of cognitive learning strategy used by the students. The result showed that, on average 58.04 % of all respondents using cognitive learning strategy, and 70 % or 21 of the 30 respondents used the practice to overcome the difficulties speaking. The analysis with the formula t test showed that, applying the cognitive learning strategy had significant positive impact on developing the learners’ ability to speak English. This was indicated by the average value before and after treatment (73 and 85.25) and obtained the distribution t table 2.000 with t calculate 5.467 obtained greater than t table.